Old orogen–young topography: lithological contrasts controlling erosion and relief formation in the Bohemian Massif - J. Robl; F. Dremel; K. Stüwe; S. Hergarten; C. von Hagke; D. Fabel (Earth Surface Dynamics)
In several low mountain ranges throughout Europe, high-grade metamorphic and granitic rocks of the Variscan orogen are exposed – even though the topography of this Paleozoic mountain range was largely leveled during the Permian and later covered by sediments. The Bohemian Massif is one of these low mountain ranges and consists of high-grade metamorphic and magmatic rocks that dip southward below the weakly consolidated Neogene sediments of the Alpine Molasse Basin. Morphologically, the Bohemian Massif is characterized by rolling hills and extensive low-relief surfaces above 500 m, which contrast with deeply incised canyons characterized by steep and morphologically active valley flanks. These morphological features and the occurrence of marine sediments several hundred meters above sea level are a clear indication of relief rejuvenation due to significant surface uplift during the last few million years.